Some Properties of Kenmotsu Manifolds Admitting a New Type of Semi-Symmetric Non-Metric Connection - Singh, Abhishek; Das, Lovejoy S.; Prasad, Rajendra; Kumar, Lalit (Communications in Mathematics and Applications, 2024)
In this paper, we study some properties of Kenmotsu manifolds admitting a semi-symmetric non-metric connection. Some curvature's properties of Kenmotsu manifolds that admits a semi-symmetric non-metric connection are obtained. Semi-symmetric, Ricci semi-symmetric and locally \(φ\)-symmetric conditions for Kenmotsu manifolds with respect to semi-symmetric non-metric connection are also studied. It is proved that the manifold endowed with a semi-symmetric non-metric connection is regular. We obtain some conditions for semi-symmetric and Ricci semi-symmetric Kenmotsu manifolds endowed with semi-symmetric non-metric connection \(\widetilde{ abla}\). It is further observed that the Ricci soliton of data \((g,ξ,Θ)\) are expanding and shrinking respectively for semi-symmetric and Ricci semi-symmetric Kenmotsu manifolds admitting a semi-symmetric non-metric connection.